The Epidemic of Non-communicable Diseases in Jamaica: Monsters Awoken from Lifestyle Practices - Paul Andrew Bourne; Cynthia Francis; Charlene Sharpe-Pryce; Angela Hudson Davis; Ikhalfani Solan (International Journal of Medical Research, 2014)
Objectives: The study was conducted to evaluate health indices of those in the retirement aged cohort and working aged cohort; to determine rates of comorbidities for those in the retirement aged and the working aged cohorts, compute the prevalence rate occurring to specific chronic non-communicable diseases and calculate death rates for those in retirement aged and the working aged cohorts. Methods: Jamaica Survey of Living Conditions (JSLC) is a national cross-sectional probability survey that is conducted yearly by two governmental agencies in Jamaica. The current sample is 4,313 Jamaicans who are either in the working or retirement aged cohort from 2007 JSLC survey as well as death statistics from 2002-2008. Results: In 2007, the prevalence rate of deaths that occur due to CNCDs is 50.7% (male, 45.2%; female, 59.5%); 12% of those in the working aged population indicate having an illness compared to 43.2% of those in the retirement aged cohort; 23.7% of retirement aged cohort reported having diabetes compared to 15% of those in the working aged cohort, and 1.6 times more of those in the retirement aged cohort imply having hypertension than those in the working aged cohort. The rate of comorbidity is 20.6% (retirement aged cohort, 27.4%; working aged cohort, 15.6%). The prevalence rate of those with CNCDs is 37.6% for those in the retirement aged cohort and 8.2% for those in the working aged cohort. Conclusion: It is imperative that age, gender, area of residence specific and culturally relevant policies be developed in order to effectively address these health matters, without delay.